Genome analysis of Lactiplantibacillus plantarum and Levilactobacillus brevis isolated from traditionally fermented Ethiopian kocho and their probiotic properties - Guesh Mulaw; Teklemichael Tesfay; Tesfaye Sisay; Diriba Muleta; Débora Brito Goulart; Olabisi Flora Davies-Bolorunduro; Chioma Ohaeri; Nirupama Narayanan (PLoS ONE, 2026)
Probiotics are essential for promoting health, with lactic acid bacteria (LAB) from traditional fermented foods like Ethiopian kocho offering valuable benefits. The objective of this study was to systematically analyse the genomic characteristics, bacteriocin production, and probiotic potential of LAB strains isolated from fermented Ethiopian kocho. LAB were isolated from kocho and screened for probiotic properties following standard methods. For the potent isolates, whole-genome sequencing (WGS) was conducted to investigate genetic relatedness. Out of 150 LAB isolates, 7 (4.67%) exhibited remarkable acid tolerance by surviving at rates between 50.52–74.05% and 33.33–62.40% after 3 and 6 hours of exposure to pH 2, respectively. These seven acid-tolerant isolates also demonstrated exceptional resistance to 0.3% bile salt, maintaining survival rates ranging from 88.96% to 98.10% over 24 hours. In addition, the isolates displayed inhibitory effects against several important foodborne pathogenic bacteria, underscoring their potential as natural antimicrobial agents. Antibiotic susceptibility testing revealed that all the isolates were susceptible to ampicillin, tetracycline, and erythromycin, whereas the most potent isolates exhibited significant resistance to kanamycin. The WGS analysis revealed that the isolates belonged to the Lactobacillus genus, including six Lactiplantibacillus plantarum strains and one Levilactobacillus brevis strain. Genomic analysis using the Bayesian Analysis of Gene Essentiality (BAGEL) tool predicted the presence of two class II bacteriocins across all the seven strains, further supporting their potential as functional probiotic candidates. Analysis of the isolates using Abricate with the Virulence Factor Database (VFDB) showed that none of the strains carried putative virulence factors. Moreover, screening for antibiotic resistance genes revealed no resistance determinants, suggesting a low risk of resistance gene transfer. Overall, these results confirm the favorable safety profile of the probiotic properties of Lactobacillus strains and support their suitability for industrial and dietary applications.